2006
DOI: 10.1152/ajpheart.00610.2005
|View full text |Cite
|
Sign up to set email alerts
|

Transport in rat vessel walls. I. Hydraulic conductivities of the aorta, pulmonary artery, and inferior vena cava with intact and denuded endothelia

Abstract: Shou, Yixin, Kung-ming Jan, and David S. Rumschitzki. Transport in rat vessel walls. I. Hydraulic conductivities of the aorta, pulmonary artery, and inferior vena cava with intact and denuded endothelia. Am J Physiol Heart Circ Physiol 291: H2758 -H2771, 2006. First published May 26, 2006 doi:10.1152/ajpheart.00610.2005In this study, filtration flows through the walls of the rat aorta, pulmonary artery (PA), and inferior vena cava (IVC), vessels with very different susceptibilities to atherosclerosis, were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 40 publications
5
45
1
Order By: Relevance
“…Tompkins simplified geometric model yielded a factor of 3: that the PA media diffusivity far exceeds that of the aorta is consistent with a variety of evidence that the PA is far sparser and more permeable to both water and macromolecules than the aorta: the PA has a far higher L pt * than the aorta (45). The in vitro experiments of Lever and Jay (34) showed that the PA wall has a greater distribution volume albumin than systemic arteries.…”
Section: Derived Parameter Valuessupporting
confidence: 61%
See 4 more Smart Citations
“…Tompkins simplified geometric model yielded a factor of 3: that the PA media diffusivity far exceeds that of the aorta is consistent with a variety of evidence that the PA is far sparser and more permeable to both water and macromolecules than the aorta: the PA has a far higher L pt * than the aorta (45). The in vitro experiments of Lever and Jay (34) showed that the PA wall has a greater distribution volume albumin than systemic arteries.…”
Section: Derived Parameter Valuessupporting
confidence: 61%
“…Given their different ⌬P*, it is not a priori obvious which experiences the higher fluid flux. Shou et al (45) found this flux, wall L p * ϫ ⌬P*, was the same in the aorta, PA and even the inferior vena cava, to within experimental error. Shou et al (46) found the rat PA endothelium also leaks HRP focally, not uniformly, over a 4-min circulation and PA and aorta focal HRP spot growth with HRP circulation time are both rapid and surprisingly similar to each other and to the aorta study of Chuang et al (9).…”
Section: Tracer Entry and Accumulation In The Aortamentioning
confidence: 68%
See 3 more Smart Citations